Interventions for breastfeeding-related nipple pain or injury: a meta-analysis - Xuyan Jia; Xuyan Jia; Yang Dong; Cuili Shen; Yuanyuan Cai; YiTing Xu; Lina Yang; Jiayue Jiang; Tong Sun; Wenhui Lu; Rong Huang (Frontiers in Global Women's Health, 2025)
BackgroundNipple pain or injury is one of the main reasons many mothers stop breastfeeding. We integrated existing literature and conducted a quantitative evaluation of efficacy, with the aim of identifying effective clinical interventions for alleviating breastfeeding-related nipple pain and injury, and providing evidence-based recommendations for future research and clinical practice. In our study, non-specific interventions are defined as measures that do not specifically provide breastfeeding support and are designed to exclude natural factors or induce placebo effects. Conversely, interventions that target the study outcomes and have standardized operational procedures are referred to as specialized interventions.MethodsWe conducted a systematic literature search across 9 databases, including MEDLINE (via Ovid), PubMed, Web of Science, CINAHL (via EBSCO), EMBASE, the Cochrane Library, CNKI, SinoMed, and Wanfang. Two independent reviewers screened the publications and extracted the data. We evaluated the quality of literature on randomized controlled trials (RCTs) and quasi-experimental clinical trials using the Cochrane Systematic Evaluation Risk of Bias Assessment Tool and the JBI Critical Appraisal Tool. After completing the quality assessment of the literature, we performed a meta-analysis using Stata 17.0.ResultsA total of 18 studies were identified in the meta-analysis. The results of the meta-analysis showed that specialized interventions were significantly better than non-specific interventions in preventing and treating nipple pain and injury associated with breastfeeding. The specialized interventions were effective in reducing the incidence of nipple pain [OR = 0.366, 95% CI (0.155, 0.862), Z = −2.301, p = 0.021 < 0.05], nipple pain scores [SMD = −0.451, 95% CI (−0.748, −0.154), Z = −2.978, p = 0.003 < 0.05], incidence of nipple injury [OR = 0.316, 95% CI (0.231, 0.433), Z = −7.177, p < 0.001], and intensity of nipple injury [SMD = −0.964, 95% CI (−1.404, −0.525), Z = −4.303, p < 0.001].ConclusionThis study shows that specialized interventions for breastfeeding-related nipple injury and pain are significantly more effective than non-specific interventions. It also demonstrates that preventive measures initiated before nipple pain onset are more effective than post-pain interventions.Systematic Review Registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD420251045411, PROSPERO CRD420251045411.